2022
DOI: 10.1001/jamanetworkopen.2022.37783
|View full text |Cite
|
Sign up to set email alerts
|

Association Between In-Person vs Telehealth Follow-up and Rates of Repeated Hospital Visits Among Patients Seen in the Emergency Department

Abstract: ImportanceFor patients discharged from the emergency department (ED), timely outpatient in-person follow-up is associated with improved mortality, but the effectiveness of telehealth as follow-up modality is unknown.ObjectiveTo evaluate whether the rates of ED return visits and hospitalization differ between patients who obtain in-person vs telehealth encounters for post-ED follow-up care.Design, Setting, and ParticipantsThis retrospective cohort study included adult patients who presented to either of 2 in-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Although the findings of the study by Shah et al may be viewed as a potential setback in the virtual care revolution, they should instead be seen as a call for more study into how to optimally use virtual care-based technologies. For instance, are there specific conditions or disease states that can be managed with virtual care?…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Although the findings of the study by Shah et al may be viewed as a potential setback in the virtual care revolution, they should instead be seen as a call for more study into how to optimally use virtual care-based technologies. For instance, are there specific conditions or disease states that can be managed with virtual care?…”
mentioning
confidence: 92%
“…In their study, Shah and colleagues 2 performed a retrospective cohort assessment of more than 16 000 unique emergency department (ED) encounters within an integrated academic health care system to examine whether the rates of ED return visits and hospitalization differed between patients who obtained in-person or telehealth post-ED discharge follow-up. 2 Using multivariable logistic regression to adjust for known confounders that are associated with telehealth and ED utilization, the authors found that post-ED discharge telehealth follow-up visits were associated with an increased rate of return visits to the ED (28.3 more returns per 1000 encounters) and hospitalization (10.6 more hospitalizations per 1000 encounters) compared with in-person follow-up visits. While the study has some notable limitations (eg, residual confounding and lack of ability to track ED visits and hospitalization outside their health care network), the findings appear to have biological plausibility and, importantly, the potential to affect how health care systems use telehealth moving forward.…”
mentioning
confidence: 99%
See 3 more Smart Citations